Towards Implementing an Intelligent System for Securing and Monitoring using Agents - Alkhateeb, Faisal; Al-Fakhry, Zain Al-Abdeen; Maghayreh, Eslam Al; Al-Taani, Ahmad T.; Aljawarneh, Shadi (IntechOpen, 2011)
None